A POST-GRADUATE SEMINAR ON MODERN NURSING AND THE INTERNATIONAL EXPERIENCE. - Luiz Antônio de Castro Santos (Universidade Federal de Goias, 2003)
A note on a cross-disciplinary teaching experience, which took place in 2002/2003, at the Institute ofSocial Medicine of the State University of Rio de Janeiro (UERJ). Students and faculty from many fields in theHealth Sciences and the Human Sciences were able to exchange individual experiences, conceptions, theoreticalperspectives and personal viewpoints, based on the study of the beautiful institutionalization processes of Nursingin the contemporary world.